Description of four new species of Burrowing Frogs in the Fejervarya rufescens complex (Dicroglossidae) with notes on morphological affinities of Fejervarya species in the Western Ghats - Garg, Sonali; Biju, S.d. (Zootaxa, 2017)
The Rufescent Burrowing Frog, Fejervarya rufescens, is thought to have a wide distribution across the Western Ghats in Peninsular India. This locally abundant but secretive species has a short breeding period, making it a challenging subject for field studies. We sampled 16 populations of frogs morphologically similar to F. rufescens in order to understand the variation among populations found across the Western Ghats. Our study shows significant morphological and genetic differences among the sampled populations, suggesting that F. ‘rufescens’ is a complex of several undescribed species. Using evidence from morphology and genetics, we confirm the presence of five distinct species in this group and formally describe four as new. The new species were delineated using a phylogeny based on three mitochondrial genes (16S, COI and Cytb) and a haplotype network of a nuclear gene (Rag1). Hereafter, the distribution of F. rufescens is restricted to the state of Karnataka and adjoining regions of northern Kerala. Three new species (Fejervarya kadar sp. nov., Fejervarya manoharani sp. nov. and Fejervarya neilcoxi sp. nov.) are from regions south of Palghat gap in the state of Kerala, and one (Fejervarya cepfi sp. nov.) from the northern Western Ghats state of Maharashtra. These findings indicate that Fejervarya frogs of the Western Ghats are more diverse than currently known. Our results will also have implications on the conservation status of F. rufescens, which was previously categorized as Least Concern based on its presumed wide geographical distribution. Furthermore, in order to facilitate a better taxonomic understanding of this region’s fejervaryan frogs, we divide all the known Fejarvarya species of the Western Ghats into four major groups—Fejervarya nilagirica group, Fejervarya rufescens group, Fejervarya sahyadris group and Fejervarya syhadrensis group, based on their morphological affinities.